Problematika Guru dalam menerapkan Pendidikan Kepramukaan Wajib sesuai Kurikulum 2013 di SDN 26 Watang Palakka - Muhammad Iwan; Sidrah Afriani Rachman; Rukayah Rukayah; Ritha Tuken (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The problem in this study is to find out the description of the teacher's problems in implementing compulsory scouting education according to the 2013 curriculum at SDN 26 Watang Palakka. This research is a descriptive qualitative research that aims to determine the perception of teachers in implementing compulsory scouting education, to describe the problems of teachers in implementing compulsory scouting education and to describe the solutions to the problems of teachers in implementing compulsory scouting education. The data analysis technique uses three stages, namely data reduction, data presentation and conclusions. Then the results of the data analysis show that first, the application of compulsory scouting education according to the 2013 curriculum at SDN 26 Watang Palakka has been implemented using three models, namely the block model, the actualization model and the regular model. Second, the inhibiting factors for implementing compulsory scouting education according to the 2013 curriculum at SDN 26 Watang Palakka, Bone Regency, namely the limitations of scouting tools, lack of teacher competence regarding scouting knowledge and the existence of the Covid-19 pandemic So it can be concluded that the solution to the inhibiting factors for the implementation of compulsory scouting education is in accordance with the 2013 curriculum at SDN 26 Watang Palakka, Bone Regency, namely Procurement of Scout Equipment, attending Basic Advanced Courses (KMD) and Advanced Advanced Courses (KML) and the application of Distance Learning (PJJ). implemented during the Covid-19 pandemic.